Some aspects of legal liability for offenses related to illegal handling of firearms in Ukraine - Verbitska, Mariana; Hnativ, Mykhailo (Actual problems of law (Aktual'ni problemi pravoznavstva), 2021)
The article is devoted to the peculiarities of handling weapons in accordance with current criminal and administrative legislation. Special attention is paid to the characteristics of responsibility for handling weapons in accordance with current legislation. The main problems related to understanding the nature and use of weapons in administrative proceedings are highlighted. Attention is focused on the relevance of this topic in the present.